Activity Level and Sport Type in Adolescents Correlate with the Development of Cam Morphology. Issue 4 (October 2021) - Westermann, Robert W.; Scott, Elizabeth J.; Schaver, Andrew L.; Schneider, Anthony; Glass, Natalie A.; Levy, Steven M.; Willey, Michael C.
Abstract : Background: The purpose of this study was to evaluate the influence of the volume and type of sport on the development of cam-type femoroacetabular impingement and acetabular dysplasia. Methods: The Physical Activity Questionnaire for Adolescents (PAQ-A) was administered to Iowa Bone Development Study participants at the age of 17 years to identify those who had participated in at least 2 seasons of high school interscholastic sports. Based on relative peak strain and ground reaction forces, subjects were grouped as power sport athletes (basketball, cheerleading, football, gymnastics, soccer, and volleyball), non-power sport athletes (wrestling, baseball, cross-country or track and field, softball, or tennis), or non-athletes. Using anteroposterior views of the left hip formatted from dual x-ray absorptiometry (DXA) scans, the alpha angle, head-neck offset ratio (HNOR), and lateral center-edge angle (LCEA) were evaluated longitudinally at the ages of 17, 19, and 23 years. Logistic regression was used to evaluate the odds of hip cam morphology (alpha angle >55° and/or HNOR <0.17) or acetabular dysplasia (LCEA <24°) at the age of 23 years in all athlete groups. The relationships between physical activity level and hip measures (alpha angle, HNOR, and LCEA) from the ages of 17 to 23 years were examined using linear mixed models adjusted for sex. Results: Compared with non-athletes at the age of 23 years, power sport athletes had significantly greater odds of cam morphology according to the alpha angle (odds ratio [OR], 2.93 [95% confidence interval (CI), 1.02 to 8.41]; p = 0.046) and HNOR (OR, 1.91 [95% CI, 1.01 to 3.60]; p = 0.047), but not greater odds of acetabular dysplasia (p > 0.05). There were no significant differences in the odds of cam morphology or acetabular dysplasia in non-power sport athletes compared with non-athletes (all p > 0.05). Higher physical activity levels were significantly associated with an increase in the alpha angle (beta and standard error, 0.77° ± 0.30°; p = 0.011) and a decrease in the HNOR (−0.003 ± 0.001; p = 0.003), but not the LCEA (−0.05 ± 0.15; p = 0.744). Conclusions: A higher volume of physical activity and participation in sports with higher peak strain and ground reaction forces during the process of skeletal maturation may increase the risk of developing cam morphology during late adolescence. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.